Isothermal Oxidation Behaviour of Heat-treated Fe-33Ni-19Cr Series Ni-based Superalloy - Megat Farhan Nazmi Megat Mohamad Halim; Noraziana Parimin; Esah HamzaH, (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
The impact of heat treatment on the high temperature oxidation of Ni-based superalloys, specifically the Fe-33Ni-19Cr series, is discussed in this study. This alloy, designated LT950 and HT1160, is heat treated at two distinct temperatures, 950 °C and 1150 °C, for three hours of soaking time, followed by a water quench. Rockwell hardness tests and optical microscopy were used to characterize the heat-treated samples. An isothermal oxidation test was performed on the heat-treated samples for 200 hours at 900 °C. The oxidation kinetics were ascertained by measuring the weight change of the oxidized sample. Oxidized samples were characterized by morphological analysis of the oxide scale using a scanning electron microscope (SEM) and oxide phase analysis using x-ray diffraction (XRD). As a result, the sample's grain size increases with increasing heat treatment temperature. The results of the Rockwell hardness test indicate that the Rockwell hardness number decreases as the heat treatment temperature rises. However, every heat-treated sample that was put through the isothermal oxidation test displayed a pattern of weight gain as the length of exposure increased. Because fine-grained LT950 has a lower parabolic rate constant, it indicates a lower rate of oxidation and therefore has good resistance to oxidation. XRD analysis shows that several oxide layers have formed on the surface of the oxidized sample consisting of Cr-containing oxides from the Cr2O3 and MnCr2O4 phases. SEM analysis of fine-grained LT950 showed uniform oxide scale, while coarse-grained HT1150 showed the formation of cracked and porous structures.